Optimalisasi Pengelolaan Sumber Daya Manusia untuk Meningkatkan Mutu Sekolah di SD Muhammadiyah Condongcatur - Alya Raihan Fadilla; Nisa Aprilia; Nurfah Zain Suyuti; Wiji Hidayati; Dewi Ratnasari (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
The quality of a primary education institution is determined not only by the quality of teachers as educators but also by the entire ecosystem of human resources (HR) within it, including education support staff such as administrative personnel, security teams, and operational workers. However, HR management in elementary schools frequently faces real challenges, such as sub-optimal workforce planning, budget constraints for equitable competency development, and performance evaluation systems that remain a mere formality. These various obstacles demand an integrated, systematic, and quality-oriented HR governance approach to optimize the roles of all school community members.This study aims to analyze the optimization of human resource management in improving school quality at SD Muhammadiyah Condong Catur. This study employs a qualitative, descriptive approach, using interviews with the Vice Principal for Curriculum as the primary informant for data collection. The results of the study indicate that human resource management is carried out systematically through several key aspects, namely recruitment, competency development, as well as performance management and welfare. The recruitment process is conducted independently through comprehensive stages, including needs analysis, administrative screening, written tests, interviews, teaching practice, and psychological assessments, thereby producing educators who align with the school’s needs. In terms of competency development, the school routinely conducts training at the end of each semester covering the enhancement of both academic and non-academic competencies, such as technology training (coding and artificial intelligence) and the cultivation of professional attitudes among teachers. Additionally, the school facilitates academic qualification enhancement through collaboration with universities. In terms of performance management, evaluations are conducted through a digital-based system with structured indicators, along with the consistent application of work discipline. The optimization of human resource management has led to improved school quality, as demonstrated by various. In terms of performance management, evaluations are conducted through a digital system with structured indicators, along with the consistent enforcement of work discipline. The optimization of human resource management has led to improved school quality, as evidenced by various achievements at the national level and the establishment of a work culture grounded in Islamic values. Thus, optimal human resource management is a key factor in improving the quality of education in elementary schools.Keywords: Human resource management, recruitment, teacher competency development, educational quality, elementary school.